Compilation of the State Financial Management System of the Ali Bin Abi Thalib Period and its Implications for Justice-Based Budget Reform in 2026 - Nihro Afandi; Naila Septiana Camelia (Lembaga Pengembangan Kinerja Dosen, 2026)
This study explores in depth the compilation of the state financial management system during the reign of Caliph Ali bin Abi Talib (656–661 AD) and its relevance to the dynamics of justice-based budget reform in 2026. Amid global economic uncertainty and increasing demands for fiscal transparency, the management model of the Baitul Maal of the Ali era offered an important paradigm regarding the equitable distribution of wealth and strict bureaucratic oversight. The research method used is qualitative descriptive with a historical-analytical approach. The results of the study show that Ali's policies in removing elite privileges, conducting periodic audits of local officials, and the principle of